Improving Business Performance through Innovation Strategy and Total Quality Management practice: Survey on the Pharmaceutical Industry In Indonesia - Yuli Fitriyani Syoemantri; Yudi Azis; Irvan Rivani; Umi Khaltum; John Sihotang (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2021)
The main purpose of this research is to analyze the relationship between innovation strategy and Total Quality Management in improving business performance. The object study of this research is pharmaceutical Industries in Indonesia. This research reveals the proper innovation strategy execution and effective implementation of Total Quality Management in business performance improvement. In this context, data collected from 168 managers at 42 firms operating in pharmaceutical industry in Indonesia were analyzed. The partial least squares structural equation modeling (PLS-SEM) method is used to test the hypotheses both of reflective and formative construct with second order/higher order construct in our model of study. The findings support the hypothesis that there is a positive and significant effect of innovation strategy and Total Quality Management on improving business performance of the company. The result of this research will have strategic implications for the company and expect to be used as feedback related to the execution of their innovation strategies and TQM implementation promptly to improve their business performance.